PENDIDIKAN DAN PELAYANAN KESEHATAN PADA LANSIA DI POSYANDU LANSIA DESA GAYAMAN – MOJOANYAR - Nurun Ayati Khasanah; Ferilia Adiesti; Citra Adityarini Safitri; Sulis Diana; Sarliana (Jurnal Pengabdian Masyarakat, 2024)
The elderly population according to age groups can be grouped into three, namely young elderly (60-69 years), middle elderly or middle elderly (70-79 years), and old elderly (80 years and over) where individuals who are already at an advanced age often experience various problems such as lack of passion for life caused by a social and physical environment that does not support activity because due to the increasing age of a person, in general the more diseases suffered, so it is not surprising that many elderly suffer from serious illnesses. The purpose of this community service is to improve the quality of life of the elderly. The materials and methods used are health education on how to do physical activity at home. The results obtained are able to know the benefits of finger exercises to improve the quality of life of the elderly. The conclusion is the importance of maintaining the health of the elderly by doing several activities such as gymnastics and routine checks carried out at one of the Elderly Posyandu in Mojokerto district. Suggestions from this community service activity so that the implementation of physical activity through finger exercises can be done every day at home in order to prevent and slow down diseases suffered by the elderly